Calvinism and the making of the European mind - Brink, Gijsbert van den, 1963- (Studies in Reformed Theology, 2014)
Calvinism must be assigned a significant place among the forces that have shaped modern European culture. Even now, despite its history of religious fragmentation and secularization, Europe continues to bear the marks of a pervasive Calvinist ethos. The character of that ethos is, however, difficult to pin down. In this volume, many of the traditional scholarly conundrums about the relationship between Calvinism and the cultural history of Europe are revisited and re-investigated, to see what new light can be shed on them. For example, how has the ethos of Calvinism, or more broadly the Reformed tradition, affected economic thinking and practice, the development of the sciences, views on religious toleration, or the constitution of European polities? In general, what kind of transformations did Calvinism's distinct spirituality bring about? Such questions demand painstaking and detailed scholarly work, a fine sample of which is published in this volume.